Muslim Consumers’ Behavior And Responses Towards Halal Logo Jakim - Mahmud Zuhudi, Nurul Wahidah (2021)
Past literature had shown many cases of abused and manipulated halal logo which affects the knowledge and understanding of the consumers, that introduced to minimise doubtful transactions and confusion for Muslim consumers. This indicates an immediate study to understand the behaviour and responses of Muslim consumers towards JAKIM halal logo by focusing on their levels of halal related knowledge, awareness and confidence in their daily consumption and routines. The study explores a mixed method of phenomenology model (1994) with thematic analysis (2006) in analysing the verbatim data.